Strengthening global health education in the UAE: assessing the current landscape and future directions - Ali Artaman; Hillani T. Bekele; Ross Millar (Frontiers in Public Health)
Global health is a growing area of interest for the United Arab Emirates (UAE). Given its location in the Middle East and its geographical proximity to developing sub-Saharan countries, the country is in a strategic position to contribute to global health agendas. Yet despite an increasing emphasis on global health policy, the availability of global health education programs at UAE universities remains limited. The aim of this Perspective is to raise awareness and understanding about the importance of the issue. Reflecting on the current landscape, it argues that it is crucial for higher education institutions in the UAE to better integrate global health into their curricula. The Perspective calls for a greater focus on curricula design, along with a further emphasis on collaboration and capacity building between universities and global health institutions to further strengthen this educational foundation.